2020
DOI: 10.1093/femsec/fiaa153
|View full text |Cite
|
Sign up to set email alerts
|

Picocyanobacteria aggregation as a response to predation pressure: direct contact is not necessary

Abstract: Picocyanobacteria (cells <2 µm) can be found either as single-cells (Pcy) or embedded in a mucilaginous sheath as microcolonies or colonies (CPcy). It has been demonstrated that phenotypic plasticity in picocyanobacteria (i.e. the capability of single-cells to aggregate into colonies) can be induced as a response to grazing pressure. The effect of the presence of different predators (cladocerans and rotifers) over the morphological composition of picocyanobacteria were studied in a natural community, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…It should also be noted that morphology and morphotypes are not stable forms. For example, single cells can aggregate (or remain attached) and form microcolonies under the presence of heterotrophic bacteria, grazing pressure, or exposure to UV radiation (Callieri et al, 2011; Cruz & Neuer, 2019; Ospina‐Serna et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that morphology and morphotypes are not stable forms. For example, single cells can aggregate (or remain attached) and form microcolonies under the presence of heterotrophic bacteria, grazing pressure, or exposure to UV radiation (Callieri et al, 2011; Cruz & Neuer, 2019; Ospina‐Serna et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…genera Aphanocapsa , Aphanothece , Chroococcus , Coelosphaerium [ 10 , 57 ]. Ospina-Serna et al [ 58 ] demonstrated that the presence of predatory cladocerans and rotifers increases the formation of colonies of individual cells. Although these colonial forms are present in Võrtsjärv, in this study they are only partly represented in PPP since the colony as a unit would not pass through the 2 μm filter.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increase in the abundance of tiny cells resembling Pcy over the last decades was apparent while quantifying nano-and micro-phytoplankton under the inverted microscope (I. Izaguirre, personal communication). On the other hand, Pcy cells often aggregate to form microcolonies in response to different stimuli [45,46], and there is typically a positive relationship between the abundance of microcolonies and that of single Pcy cells. Our historical records of microcolonies abundance for a few Pampean lakes from 1987 [47] to 2015 [48,49] show remarkable abundance increases.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in plankton composition might alter the trophic interactions, and consequently the flow of matter and energy through the food web. For instance, certain species of zooplankton mediate the phenotypic plasticity of Pcy, promoting their aggregation into colonies [44][45][46]. The decrease in the average cell size of phytoplankton would enhance the relative importance of intraguild predators at intermediate trophic levels of the food web, favoring the heterotrophic microbial pathway through small protists with the increase in complexity and consequent reduction in trophic efficiency, as it occurs in large tropical lakes [4].…”
Section: Discussionmentioning
confidence: 99%